Implications of Accountants Unethical Behavior and Corporate Failures - Eshiet, Udeme Enobong (International Journal of Business, Economics and Management, 2017)
Purpose/objective: Emphasis on short term profit and share prices as criteria for the determination of business success have led to attrition of stakeholder trust and unlocked the doors for unethical conducts by professional accountants. Acceptable ethics and encounters of accountants are very critical in the global market place. This study was undertaken to advocate high ethical practices by accountants to protect the interest of the stakeholders. Methodology/approach: A literature review of fifteen scholarly peer-reviewed journal articles on corporate scandals caused by unethical behaviors of corporate leaders and accountants. Findings: (1) Unethical practiced by accountants have unintended consequences globally; (2) The accounting profession has suffered severe image damages as a result of unethical behaviors by corrupt accountants; (3) Unethical behaviors by accountants significantly contributed to the global corporate scandals, the Nigerian banking sector reorganization, and the extinction of some global companies from 2002 - 2009; (4) With the right corrective measures, organizations plagued with scandals can survive ethical challenges; (5) Audit committees oversight functions are critical in preventing corporate scandals; (6) (Un) ethical behaviors by professional accountants, organizational leaders is a tenable leadership theory. Implications/research limitations: This study, grounded in conceptual framework of business ethics, addressed the implications of unethical behaviors by accountants. This research examined the penalties of immoral conducts by accountants and organizational leaders citing Tyco International scandal as case study. Implications are that unethical behaviors by accountants have unintended consequences on stakeholders. Unethical behaviors by accountants contributed to global corporate scandals, the Nigerian banking sector reorganization, and the extinction of some global companies from 2002 – 2009. For imminent studies, effort should be made to include other relevant literature into the study.